The effect of book income adjustment in the 1986 alternative minimum tax on corporate financial reporting - Dhaliwal, Dan; Wang, Shiing-wu (Journal of Accounting and Economics, 1992)
This study examines the effect of the book income adjustment provision in the 1986 alternative minimum tax (AMT) on financial accounting practices. A model is developed to identify firms that are more susceptible to the book income adjustment. The changes in financial accounting practices for firms affected by the AMT are then examined. Our results indicate that firms that are likely to be affected by the book income adjustment shift timing and permanent differences across years to reduce the impact of the AMT.